1991
DOI: 10.1111/j.1464-410x.1991.tb15163.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Retention of Urine: A Reappraisal

Abstract: Our standard policy for the management of retention of urine due to prostatic hypertrophy is that the patient is catheterised and sent home, later to be seen and assessed in the Out-patient Department where he is given an admission date for operation. A detailed audit of 166 patients cared for in this way is presented and the results compared with those in 25 patients who remained in hospital in the interval between catheterisation and operation and in 402 patients not previously catheterised. Although the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In one study, 88% of catheterized patients underwent a TURP within 3 months [6]. Another British study reported the mean duration of catheterization from AUR to TURP at 7.8 weeks [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, 88% of catheterized patients underwent a TURP within 3 months [6]. Another British study reported the mean duration of catheterization from AUR to TURP at 7.8 weeks [7].…”
Section: Discussionmentioning
confidence: 99%
“…This group of patients are also more likely to develop post-operative UTIs and to require antibiotics, most likely as a result of prolonged catheterization [6]. Another group found the mortality rate after TURP in patents with an indwelling catheter to be significantly higher than in patients without a catheter (3.3% vs. 0.25%) [7].…”
Section: Discussionmentioning
confidence: 99%
“…48 It is not without risk, however, and if patients who have had an episode of AUR have a TURP they are at a higher risk of per-operative complications. 49 The National Prostatectomy Audit found that men undergoing a TURP within 30 days of an episode of AUR had an excess risk of death (relative risk 26.6, CI 2.5-7.6). 20 With greater insight into the potential morbidity and occasional mortality associated with this procedure, alternatives have been sought in the form of pharmacotherapy and minimally invasive techniques.…”
Section: Surgical Interventionmentioning
confidence: 99%
“…Transurethral resection of the prostate (TURP) can be performed safely on most patients who present with retention of urine. However, the operative mortality rate is higher in patients with retention than in those who undergo the operation for symptomatic outflow obstruction (1.9 us 3.3%) (Higgins et al, 1990). This rate increased to over 5% in those over 80 years old (Wyatt et al, 1989).…”
mentioning
confidence: 98%